Proses Pemecahan Masalah Numerasi Calon Guru MI pada Konten Geometri dan Pengukuran Ditinjau Berdasarkan Tingkat Kemampuan Matematis - Seftyana Ayu Susanti (Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
Numeracy problems are challenging non-routine tasks presented in the form of story problems using real situations in everyday life related to a particular context and cannot be solved with existing procedures. The process of solving numeracy problems will differ from one student to another, which can be influenced by several factors, one of which is the level of mathematical ability. This study is a descriptive study with a qualitative approach that aims to describe the numeracy problem-solving process of prospective MI teachers based on the level of mathematical ability grouped into high and low levels of mathematical ability. The subjects in this study were two female students with high and low levels of mathematical anxiety. Data collection was carried out in writing using numeracy problem-solving tasks and interviews. The results of this study indicate that students from each category of mathematical ability levels in carrying out the numeracy problem-solving process fulfill each indicator of the problem-solving process used in this study.